The Effect of Price and Brand Image on Purchase Decision Moderated Digital Marketing - Angel Luky Permatasari; Survival; Wahju Wulandari (Optima Science, 2024)
This study to test a model develop to explain the effect of price and brand image on purchase decision with moderated digital marketing at mobile legends user in Malang City. This study aims to provide a deeper understanding of the factors that influence purchasing decisions in the online gaming industry, especially mobile legends games for mobile legends game users in Malang. By analyzing the influence of price and brand image on purchasing decisions moderated by digital marketing. This study use a survey method with a quantitative research method. This study uses primary data. Primary data is data collected directly by researchers from their sources The analytical techniques in this study used descriptive and inferential statistical analysis techniques. The research results show that (1) Good prices cannot increase purchasing decisions. (2) An excellent brand image can improve purchasing decisions. (3) Good digital marketing can improve purchasing decisions. (4) Good prices cannot increase purchasing decisions with Digital Marketing mediator. (5) A good brand image cannot improve purchasing decisions with Digital Marketing mediator.